Predictors of PTSD and CPTSD in UK firefighters. Issue 1 (1st January 2021) - Langtry, John; Owczarek, Marcin; McAteer, Donal; Taggart, Laurence; Gleeson, Christina; Walshe, Catherine; Shevlin, Mark
ABSTRACT: Background : Globally, professional firefighters are often exposed to traumatic events and are at high risk of developing posttraumatic stress disorder (PTSD) symptoms. Objective : With the publication of the 11th edition of the International Classification of Diseases (ICD-11) there arose a need for research based on the new diagnostic criteria, and the associated disorder, Complex PTSD (CPTSD). Method : Participants were 1300 former or present firefighters from the UK. Prevalence rates of PTSD and CPTSD were estimated using International Trauma Questionnaire in accordance with ICD-11 criteria, and service related and personal trauma exposure were also assessed using an anonymous online questionnaire. Multinomial logistic regression was performed to assess how service and personal trauma exposure predicted PTSD and CPTSD. Results : CPTSD criteria were met by 18.23% (95% CI 16.13–20.33%) and PTSD criteria were met by 5.62% (95% CI 4.37–6.87%) of the sample. Experiencing higher levels of service-related trauma significantly increased the risk for both PTSD and CPTSD, and nonwork related trauma uniquely predicted CPTSD but not PTSD. Conclusions : This study provided the first examination of the new ICD-11 criteria for PTSD and CPTSD in a large sample of firefighters, and CPTSD was more common than PTSD. Exposure to multiple different types of trauma increased the odds of PTSD and CPTSD. HIGHLIGHTS: Emergency service personnel are at elevated risk of stress related disorders due to the work related trauma exposure. Evidence has shown that rates of posttraumatic stress disorder (PTSD) in samples of firefighters are higher than the general population. This study aimed to assess rates of PTSD and Complex PTSD (CPTSD) in a large sample of UK firefighters. It was predicted that ongoing exposure to stressful and traumatic events as a firefighter may result in high levels CPTSD. PTSD and CPTSD were assessed using a standardised measure, the International Trauma Questionnaire, and the ICD-11 PTSD criteria were met by 5.62% of the participants, and 18.23% met the criteria for CPTSD. The experience of increased traumatic work-related events increased the likelihood of both PTSD and CPTSD, however non-work related stressors were only associated with CPTSD.